Assessment of air quality during the New Year’s Eve fireworks display in Copacabana, Rio de Janeiro, Brazil - Adriana Gioda; Marcos Felipe Pedreira; Eduarda Santa-Helena; Anna De Falco; Ana Carolina de Oliveira; Tatiana Saint’Pierre; Luciana Ventura (Academia Environmental Sciences and Sustainability, 2025)
Brazil hosts the world’s largest New Year’s Eve fireworks display at Copacabana Beach in Rio de Janeiro, attracting two million attendees yearly. City Hall enforces strict pedestrian-only access to Copacabana several hours before the event to manage this massive crowd and minimize vehicle traffic. The spectacular show begins at midnight and lasts between 12 and 17 min, utilizing 17 to 25 tons of fireworks. The impact of fireworks on air quality was assessed using monitoring data from automatic stations (PM10, SO2, CO, O3) and semi-automatic stations (PM2.5). PM2.5 samples were collected on filters and analyzed for elemental composition. A sharp increase in the PM10 concentration was observed during the fireworks display, peaking at 300 µg m−3, while gas concentrations showed no similar trend. On Jan 1, the daily PM2.5 concentration reached 48 µg m−3, remaining within the Brazilian regulatory limits. Significant increases in specific chemical elements (Cu, Pb, Cd, and Rb) and ions were linked to fireworks emissions. Although these pollution spikes are short-lived, they may pose risks to sensitive individuals.